Salience identity of women in terrorism - P., Gega Ryani Cahya Kurnia B.; Sukabdi, Zora A. (Universitas Islam Negeri Ar-Raniry, 2021)
Recently the involvement of women in terrorism has increased through their various roles, from facilitators, recruiters, nurses, couriers to suicide bombers and frontline fighters in acts of terrorism. Even though jihad limit the involvement of women in action, the rising of ISIS in 2014 has increased their involvement in terrorism as jihadists. Women are given various passive and active roles such as being the perpetrators of suicide bombers. Violent behavior by women is said to be a deviation because of gender stereotypes that exist in society and shift the view that women are victims. This study used a qualitative descriptive method with a literature study to describe the identity and role that women have in terrorism. Furthermore, this study used a theoretical analysis of Sheldon Stryker's Identity Theory (1980) with the salience identity to find out how to counter women involvement in terrorism in profiling practice to decide the methods to hadling it. The results of the study showed that the salience identity of women is still not considered as the main character in terrorism so that women are often considered as victims.The involvement of women in the role is marked by the roles they carry that affect their social behavior according to the role they play as terrorists. There are various identities of women that will have an impact on policies to deal with terrorism aimed at women, they must look at the roles and identities they have in accordance with the proportions of their salience identities.